Biosolids Effects on Phosphorus Retention and Release in Some Sandy Florida Soils - Lu, Peng; O'Connor, George A. (Journal of environmental quality, 2001)
ABSTRACT The soil solid phase components most responsible for P sorption in Florida soils are Fe and Al oxides. Thus, we hypothesized that land application of biosolids would significantly increase a soil's P retention by increasing its content of P‐sorbing solids, especially when biosolids with high Fe and Al concentrations are applied to soils that sorb P poorly. Biosolids effects were quantified by a series of single‐point isotherms on soils from two field studies sampled for up to 4 yr after initial biosolids application. Biosolids additions had little effect on P retention in a soil with abundant oxalate‐extractable Fe and Al and a correspondingly large native P‐sorbing capacity. However, biosolids significantly increased P retention in a soil with low oxalate‐extractable Fe and Al content and low native P‐sorbing capacity. Biosolids effects on P retention lasted 1 to 3 yr after application, depending on biosolids source and rate of application, and generally mimicked persistence of increased extractable Fe and Al concentrations in the poorly P‐sorbing soil. Disappearance of added Fe and Al (and, hence, P retention capacity) from the surface horizons over time was relatively rapid, perhaps due to abundant organic acid production associated with biosolids degradation. Phosphorus in biosolids containing (or tailored to contain) abundant Fe and/or Al can be expected to behave as a slowly available P source, and to be less subject to leaching losses than completely soluble P sources.